Pengembangan Strategi Promosi Program Studi Melalui Pendekatan Kolaboratif Berbasis Model Triple Helix - Jayadi, Agus (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to develop a collaborative promotional strategy for the Development Economics Study Program at Cordova University by adapting the Triple Helix approach, which involves synergy between universities, businesses, and government. Using a qualitative method with a descriptive-exploratory approach, data were collected through in-depth interviews, focus group discussions, document studies, and observations. The results indicate that the existing promotional strategy remains partial, institution-focused, and lacks coordination among units. However, there is significant potential from external factors such as alumni, local industry players, and government agencies. Alumni serve as institutional ambassadors, industry players validate the curriculum, and the government supports through policies and promotional access. The proposed promotional model positions the university as the center of academic narrative, the industry as the enforcer of job-market relevance, and the government as the connector to society. This approach addresses internal resource limitations and creates sustainable collaborative value. Although limited to one institution, this model holds potential for replication in similar contexts. Theoretically, this study expands the application of the Triple Helix model from innovation to higher education marketing strategies.